2023
DOI: 10.1136/bmjopen-2022-068792
|View full text |Cite
|
Sign up to set email alerts
|

Viral suppression and associated factors among children tested for HIV viral load at Amhara Public Health Institute, Dessie Branch, Ethiopia: a cross-sectional study

Abstract: ObjectiveThis study aims to assess viral suppression and associated factors among children tested for HIV viral load at the Amhara Public Health Institute, Dessie Branch, Ethiopia.DesignAn institutional cross-sectional study was conducted. An observational checklist was used to collect the data. Data were entered into EpiData and analysed using SPSS (V.25). The data were analysed descriptively. Variables with p=0.25 from the bivariable analysis were entered into a multivariable logistic regression model, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The studies found through database searching and included for the current review were performed between 2016 and 2022 and published between 2018 and 2023. Regarding the study area/region, 7 articles were conducted in the Amhara region [ 20 , 25–30 ], 6 studies in the Oromia region [ 21 , 31–35 ], 5 articles in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region [ 19 , 36–39 ], 1 study in the Tigray region [ 40 ], and 2 studies in the Addis Abeba city administration [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies found through database searching and included for the current review were performed between 2016 and 2022 and published between 2018 and 2023. Regarding the study area/region, 7 articles were conducted in the Amhara region [ 20 , 25–30 ], 6 studies in the Oromia region [ 21 , 31–35 ], 5 articles in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region [ 19 , 36–39 ], 1 study in the Tigray region [ 40 ], and 2 studies in the Addis Abeba city administration [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were conducted using a cross-sectional study design [ 19 , 25 , 28 , 32–35 , 37 , 39 , 40 ], 2 studies were conducted using a case–control study design [ 31 , 41 ], 8 studies were conducted using a retrospective cohort study [ 20 , 21 , 26 , 27 , 29 , 30 , 36 , 42 ], and 1 study was conducted using a prospective cohort study [ 38 ]. Nine studies were conducted on first-line ART patients [ 21 , 26 , 31 , 33 , 34 , 36 , 37 , 38 , 42 ], 9 studies were conducted on both first- and second-line ART patients [ 19 , 20 , 25 , 28 , 29 , 32 , 35 , 39 , 40 , 41 ], and 2 were conducted on second-line ART patients [ 27 , 30 ]. The minimum sample size was 152 in the study in Arba Minch [ 38 ], and the maximum sample size was 19 525 in the study in the Tigray region ( Table 1 ) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other factors were not found to be significantly associated with virological non-suppression, although they were significant in some previous studies, such as age 24 , 43 , 44 and duration of DTG regimen. 45 This shows that virological non-suppression can be associated with different factors in different populations; therefore, more studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…By study design, ten studies were conducted using a cross-sectional study design (18,24,27,31,32,33,34,36,38,39), two studies were conducted using a case control study design (30,40), eight studies were conducted using a retrospective cohort stud (19,20,25,26,28,29,35,41) and one study was conducted using a prospective cohort study (37). Nine studies were conducted on rst-line ART patients (20,25,30,32,33,35,36,37,41), nine studies were conducted on both rst-and second-line ART patients (18, 19,24,27,28,31,34,38,39,40), and two were conducted on second-line ART patients (26, 29). The minimum sample size was 152 taken in the study in Arba Minch (37), and the maximum sample size was 19,525 used in the study in the Tigray region (39) for detail (Table 1).…”
Section: Characteristics Of the Included Studies In Ethiopiamentioning
confidence: 99%
“…The study found through database searching was performed between 2011 and 2022. Regarding the study area/region, seven studies were conducted in the Amhara region (19,24,25,26,27,28,29), six studies in the Oromia region (20,30,31,32,33,34), ve studies in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region (18,35,36,37,38), one study in the Tigray region (39) and two studies in the Addis Abeba city administration (40,41).…”
Section: Characteristics Of the Included Studies In Ethiopiamentioning
confidence: 99%